Chapter Fisco e mobilità geografica. Il censimento ostiatim in un villaggio della pianura campana (1522) - Senatore, Francesco (Reti Medievali E-Book, 2021)
The paper studies a rare record: the census (numerazione dei fuochi) of Fratta piccola (today Frattaminore), a village near Naples, in 1522, focusing on the process of counting the households in the Kingdom of Naples and on the description of the families. The village had a young and dynamic demographic profile, influenced by the capital city.